2019
DOI: 10.1002/aur.2157
|View full text |Cite
|
Sign up to set email alerts
|

The social ecology of aggression in youths with autism spectrum disorder

Abstract: for their services as my research assistants. Finally, I would also like to thank all of the families who participated in this study. iii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Following the historic pattern present in ASD and sleep research, the majority of studies in the past 3 years document how sleep is associated with other aspects of context, autism, and/or development. Sleep in autism is associated with (1) demographic factors [ 75 77 ], (2) challenging behaviors [ 36 , 78 – 87 ], (3) core ASD symptoms [ 38 , 65 , 77 ], and (4) other psychiatric symptoms [ 84 , 88 , 89 ]. Studies with a developmental focus also document correlations with executive functioning [ 88 , 90 ], memory [ 91 – 93 ], attention [ 79 , 94 ], and phonological learning [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the historic pattern present in ASD and sleep research, the majority of studies in the past 3 years document how sleep is associated with other aspects of context, autism, and/or development. Sleep in autism is associated with (1) demographic factors [ 75 77 ], (2) challenging behaviors [ 36 , 78 – 87 ], (3) core ASD symptoms [ 38 , 65 , 77 ], and (4) other psychiatric symptoms [ 84 , 88 , 89 ]. Studies with a developmental focus also document correlations with executive functioning [ 88 , 90 ], memory [ 91 – 93 ], attention [ 79 , 94 ], and phonological learning [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these findings elicit further concern as studies have documented high prevalence rates of aggression in autistic youth. Estimates indicate that upwards of 50% of autistic youth experience some level of aggressive behavior (e.g., Kanne & Mazurek, 2011;Mazurek et al, 2013), with acts of physical aggression (e.g., hitting, kicking) being generally more prevalent than verbal acts of aggression (e.g., name-calling, insults; Brown et al, 2019;Farmer et al, 2015). However, unlike aggressive behavior in non-autistic youth, some studies have found that aggression in autistic children is not strongly related to youth gender, socioeconomic status, or intellectual functioning (Brown et al, 2019;Kanne & Mazurek, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive behaviors in autistic youth have been linked with challenges across multiple domains of functioning. Indeed, autistic youth who exhibit aggression may experience difficulties across their psychosocial environments including poorer family relations, lower grades, and more severe mental and physical health problems (Brown et al, 2019; Mazurek et al, 2013). Moreover, aggression can exacerbate the problems autistic youth often already experience with peers (e.g., high rates of social rejection due to mistreatment and misunderstanding by peers; Brown et al, 2019; Zeedyk et al, 2016); and it can be a precipitating factor in hospitalizations and expulsion from school (Ambler et al, 2015; Mandell, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…to experience decreased sleep quality and low coping abilities [6]. Aggressive behavior can lead to loosening of individual relationships with peers [7], leading to conflict [8], [9], [10], decreasing academic achievement [11], develop impulsive attitudes and reduce the ability to empathize [12].…”
mentioning
confidence: 99%